The gene - Stonebarger, Bill. (Time, space and spirit.)
Part one dramatizes the history of genetic research from Gregor Mendel to modern recombinant DNA. Part two outlines the basic picture scientists have today of what a gene is and how it operates within living cells. Includes material on genetic engineering and cloning.